Improved PCR-RFLP for the detection of diminazene resistance in Trypanosoma congolense under field conditions using filter papers for sample storage - Vitouley, H.S.; Mungube, E.O.; Allegye-Cudjoe, E.; Diall, O.; Bocoum, Z.; Diarra, B.; Randolph, Thomas F.; Bauer, B.; Clausen, Peter-Henning; Geysen, D.; Sidibe, I.; Bengaly, Z.; et al. (Public Library of Science, 2011)
Animal African trypanosomiasis (AAT) is caused by different species of the protozoan parasite Trypanosoma and affects a wide range of domestic animals. Trypanosoma congolense is widespread in the whole of sub-Saharan Africa and is the species causing considerable losses in livestock production, often affecting the health status of humans through endangering the food supply of rural communities. It is estimated that 50 million cattle are at risk of the disease and that the direct and indirect annual losses related to AAT reach US$4.5 billion [1]. Despite ambitious AAT control programmes such as the Pan African Tsetse and Trypanosomiasis Eradication Campaign that aim to eradicate the disease from the African continent, the control of the disease will in the foreseeable future continue to rely heavily on the use of trypanocidal drugs. Diminazene aceturate (DA) is the cheapest and most popular trypanocide. However, this drug, commercialized more than half a century ago, tends to become ineffective due to the spread of trypanocidal drug resistance now reported in 17 African countries [2]. The different techniques for the diagnosis of trypanocidal drug resistance were exhaustively reviewed by Delespaux et al. [2]. Two techniques are routinely used in the field namely, block treatments [3] and in vivo tests [4]. Block treatment involves follow-up for a period of 2 months of treated and non-treated (control) herds. This method provides information on the hazard of contracting trypanosomiasis (number of cattle becoming positive in the control group) and on the level of trypanocidal drug resistance (number of cattle becoming positive in the treated group). In vivo tests (performed in small ruminants for Trypanosoma vivax or in rodents for T. congolense) remain the gold standards but present some drawbacks, such as (i) problems associated with the growth of some T. congolense strains in rodents, (ii) the long period of follow up (2 months), and (iii) the intensive use of experimental animals. To address these important drawbacks, the Department of Animal Health of the Institute of Tropical Medicine Antwerp has been actively involved in research on trypanocidal drug resistance and in 2007 was designated Reference Centre for Livestock Trypanosomiasis, Parasite Management and Diagnosis (RCLT) by the Food and Agriculture Organization of the United Nations (FAO) and accredited to ISONORM 17025 in 2009. Here, a BclI-PCR-RFLP was developed for the molecular diagnosis of DA resistance in T. congolense [5], the most widely used trypanocidal drug. The test is based on the detection of a single point mutation in P2-type purine transporters and has been transferred to a network of regional reference laboratories in West, East, and Southern Africa for use in large-scale surveys to detect the presence of trypanocidal drug resistance throughout tsetse-infested Africa. The correlation of this PCR-RFLP with the single dose mouse test (gold standard) [4] is excellent even if the PCR-RFLP was found to be more sensitive than the single dose mouse test [5], [6]. Although the test performs very well under laboratory conditions [6], it requires further adaptation and evaluation for use under field conditions. More specifically, the test's ability to amplify low concentrations of parasite DNA (as a result of often low parasitaemias in livestock) needs to be enhanced and its specificity improved by preventing incomplete digestion of the amplicon showing the point mutation by the BclI enzyme. This incomplete digestion creates profiles consisting of partially undigested and digested amplicons (resistant) and as such, falsely mixed RFLP profiles. Finally, sample collection, storage, and transfer to regional reference laboratories need to be simplified. In view of the above, the test's ability to amplify low concentrations of DNA was enhanced by adding a step of whole genome amplification using the QIAGEN REPLI-g UltraFast Mini Kit. Its specificity was improved by replacing the BclI (T∧GATCA) enzyme by DpnII (∧GATC). Internal negative and positive controls (resistant and sensitive strains characterized by sequencing their respective amplicons) were added to ensure the absence of contamination, an effective DNA amplification, and the complete digestion of the PCR products. Finally, sample collection, storage, and transfer could be facilitated by collecting blood spots or buffy coats on filter paper (Whatman N°4, Whatman) (Figures 1 and 2). When costs and availability are not a limitation, the use of Whatman FTA or FTA Elute cards could constitute an interesting alternative, as it is believed to offer superior preservation of the DNA.